Geological Structural Control on the Distribution of Rock Alteration in Ngebel Lake and Surrounding Areas, Ponorogo, Indonesia - Andy Wijaya; Kusumayudha, Sari Bahagiarti; Yudiantoro, Dwi Fitri; Yatini; Asfahani M. G. (GoAcademica Research & Publishing, 2025)
The Telaga Ngebel Complex is an area with an active geothermal system. Geothermal energy is considered a promising alternative energy source for the future, especially in light of the depletion of fossil fuels. In geothermal exploration, altered rocks serve as indicators of the presence of a geothermal system. The existence of an active geothermal system is closely related to alteration zones, which are, in turn, influenced by geological structures. This study aims to identify the structural controls on the distribution of alteration zones. The methods used include literature review, field surveys, remote sensing, sampling of altered rocks, and collection and measurement of structural data. The results show that the study area has a high density of structural lineaments in the southern part of the lake, as evidenced by the intersection of several strike-slip faults. These intersections serve as pathways for hydrothermal fluids to ascend. The alteration found in these high-density areas is predominantly propylitic alteration. Other types of alteration observed include argillic alteration.